2017
DOI: 10.1080/07391102.2017.1291363
|View full text |Cite
|
Sign up to set email alerts
|

Scrutiny of the mechanism of small molecule inhibitor preventing conformational transition of amyloid-β42 monomer: insights from molecular dynamics simulations

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder that is characterized by loss of intellectual functioning of brain and memory loss. According to amyloid cascade hypothesis, aggregation of amyloid-β (Aβ) peptide can generate toxic oligomers and their accumulation in the brain is responsible for the onset of AD. In spite of carrying out a large number of experimental studies on inhibition of Aβ aggregation by small molecules, the detailed inhibitory mechanism remains elusive. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 136 publications
3
9
0
Order By: Relevance
“…In this regard, studies of protein aggregation by using computer simulations have providedk ey insight into the molecular mechanism of AD and can be employed to design more potent novel inhibitors. [154] Another major challenge is the lack of efficient biomarkers that can detectt he disease at an early stage. Much earlier detection of the disease could be possible by the use of neuroimaging and biomarkers in the cerebrospinal fluid or plasma.F urthermore,t he drug candidate is required to cross the blood-brain barriera nd that too in a therapeutically appropriate concentration.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, studies of protein aggregation by using computer simulations have providedk ey insight into the molecular mechanism of AD and can be employed to design more potent novel inhibitors. [154] Another major challenge is the lack of efficient biomarkers that can detectt he disease at an early stage. Much earlier detection of the disease could be possible by the use of neuroimaging and biomarkers in the cerebrospinal fluid or plasma.F urthermore,t he drug candidate is required to cross the blood-brain barriera nd that too in a therapeutically appropriate concentration.…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations were performed using the GROMACS 5.1.4 package [16] with the GROMOS96 43A1 force field [17], which has been widely used for the conformational change analysis of Aβ [18][19][20][21][22][23][24]. The Aβ42 and the docked complex of Aβ42-1BKV obtained from the HDOCK server were selected for MD simulations and the two systems were named Aβ42-APO and Aβ42-1BKV complex, respectively.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Definitely, Phe residues initiate the hydrophobic clustering of amyloid proteins and is considered central in the Aβ fibrillation process [ 12 ]. Shuaib and Goyal observed that a sulfonamide molecule stabilizes native α-helix conformation over the β-sheet form using 200 ns MD simulation [ 13 ]. Moreover, from molecular dynamic (MD) simulations it was reported that flavonoid compounds (E)-5-(4-hydroxystyryl)quinolone-8-ol, J147 derivative, and edaravone prevent the amyloid-Aβ42 conformational transition by disrupting its Asp23–Lys28 salt bridge [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%